2021
DOI: 10.1038/s41598-021-99238-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood microbial signatures in current and former smokers

Abstract: The human microbiome has a role in the development of multiple diseases. Individual microbiome profiles are highly personalized, though many species are shared. Understanding the relationship between the human microbiome and disease may inform future individualized treatments. We hypothesize the blood microbiome signature may be a surrogate for some lung microbial characteristics. We sought associations between the blood microbiome signature and lung-relevant host factors. Based on reads not mapped to the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…We created interferon scores using the RNA-seq gene expression data to observe correlation between detection of infections and host response (see “Methods”) 6 . We integrated the viral detection data with the scores for the interferon alpha and interferon gamma pathways to observe score values in the subjects with HCV detection compared with the subjects lacking viral detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We created interferon scores using the RNA-seq gene expression data to observe correlation between detection of infections and host response (see “Methods”) 6 . We integrated the viral detection data with the scores for the interferon alpha and interferon gamma pathways to observe score values in the subjects with HCV detection compared with the subjects lacking viral detection.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects were at least one month removed from an acute respiratory infection. The RNA-sequencing and data processing methods were reported previously 6 , 19 . Briefly, paired end reads with nominal 75 bp length were generated on an Illumina HiSeq 2500 flow cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics administration to mice lacking the airways secretory immunoglobulin A (IgA) inhibited the emphysema-like symptoms in these mice and reduced lung remodeling and inflammation, suggesting that the microbiome in COPD may have deleterious effects on disease progression [ 83 ]. Microbiome signals from other anatomical sites like the gut may also affect COPD progression [ 84 , 85 ].…”
Section: Microbial Dysbiosis In Smoking-associated Diseasesmentioning
confidence: 99%
“…The tobacco smoking-nicotine-cycle has been shown to be intimately connected to microbiome status [144]. For example, a recent study established that there is specific microbiome-based signature in human blood that identifies and distinguishes former and current smokers [145]. Other research groups found that former and current cigarette smokers could be distinguished from never smokers based on fecal microbiota [146].…”
Section: Who Behavior Modifications #2 and #3: Consume Less Alcohol And Stop Using Tobacco -(In Spite Of The Microbiome's Role In Addictimentioning
confidence: 99%